Anti-leakage high-thermal-conductivity composite phase change material and preparation method thereof

Through the phase change material packaging structure of one-dimensional/two-dimensional heterogeneous hybrid fillers and surface modified coating layers, the problems of insufficient thermal conductivity and poor packaging of phase change materials are solved, efficient thermal management and leakage prevention effects are achieved, and the safety and life of electronic devices are improved.

CN120248837APending Publication Date: 2025-07-04NINGBO INST OF NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202510282378.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

Existing phase change materials have problems such as insufficient thermal conductivity and poor packaging in electronic devices, resulting in poor thermal management results and easy leakage, affecting the safety and life of the device.

Method used

The phase change material packaging structure consisting of one-dimensional/two-dimensional heterogeneous hybrid fillers and continuous phase carbon sources is used to form high-efficiency heat transfer paths and good packaging through electrostatic adsorption and hydrogen bonding, and the surface modified coating layer is used to enhance leakage prevention performance.

Benefits of technology

It achieves high thermal conductivity and excellent packaging effect, significantly improves the thermal management capabilities of phase change materials, prevents leakage, and ensures the safe and stable operation of electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120248837A_ABST
    Figure CN120248837A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-leakage high-thermal-conductivity composite phase change material which comprises the following raw materials in parts by mass: 100 parts of a carbon precursor solution, 10-40 parts of a two-dimensional nanofiller, 6-24 parts of surface modified carbon nanofibers and 900-1000 parts of a phase change material. The invention further discloses a preparation method of the leakproof high-thermal-conductivity composite phase change material. The integrated amphiphilic phase change material packaging structure which is formed by the one-dimensional / two-dimensional heterogeneous hybrid filler and the continuous phase carbon source and is subjected to surface treatment can provide an efficient heat transfer path for heat conduction; and good liquid phase change material packaging is formed through the hydrogen-bond interaction of the phase change material and the surface modification coating layer, so that the leakproof performance of the structure is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of phase change materials, and particularly to a leakage-proof and highly thermally conductive composite phase change material and a preparation method thereof. Background Art

[0002] With the rapid development of integrated circuits, the performance of chips has been greatly improved, but at the same time, it has also brought the problem of a significant increase in heat generation. Severe heat accumulation will significantly delay the information transmission speed of the chips, resulting in a substantial decrease in performance. More seriously, it will accelerate the aging of the chips and even cause the failure of the chips. The reduction in chip volume has brought challenges in high heat flux density heat dissipation, making traditional heat dissipation methods (such as air cooling and liquid cooling) difficult to meet the requirements. Therefore, a more efficient chip thermal management method is urgently needed.

[0003] Solid-liquid phase change materials are considered reliable energy storage media because of their excellent energy storage density and small volume change characteristics, and have great potential in the thermal management applications of electronic devices. Nevertheless, the low thermal conductivity of the phase change material itself will cause the heat generated by the device to be difficult to conduct quickly through the phase change material, and at the same time, the overflow and leakage of the phase change material during the phase change process may also damage the electronic device. Therefore, modern electronic device thermal management requires that the phase change material has high thermal conductivity and shape stability at the same time to achieve efficient temperature control of the device and ensure its safe operation.

[0004] To improve the thermal conductivity of the phase change material, thermal conductive fillers can be introduced into the phase change material. If the thermal conductive filler is only introduced by simple mixing with the phase change material, it is difficult to prevent the leakage of the phase change material and cannot meet the requirements for long-term use under the thermal management conditions of the phase change material. Therefore, the solid-liquid phase change material needs to be encapsulated during use. Among many encapsulation methods, three-dimensional porous structure encapsulation is widely used because it can not only accommodate more phase change materials, but also the rich thermal conductive pathways can limit the volume change of the phase change material during the phase change process at the same time. Liu Zhaowei of Xi'an University of Technology (CN118580840B) prepared a composite phase change material by constructing a BN fiber aerogel and loading PEG@SiO2 microcapsules in the aerogel. Although a certain encapsulation effect of the phase change material was obtained, there was still serious phonon scattering at the interface between the microcapsules and the aerogel skeleton, and its thermal conductivity was still not enough to meet the actual use requirements. Li Baoan of Nankai University (CN118344850A) embedded a porous MXene-Co aerogel into a graphene array to obtain a three-dimensional graphene-magnetic particle hybrid skeleton. After being compounded with the phase change material, the thermal conductivity of the composite material was improved. At present, the phase change composite material containing a three-dimensional porous thermal conductive structure still has problems of insufficient thermal conductivity and insufficient encapsulation of the phase change material.

[0005] Therefore, there is an urgent need to develop a framework structure with excellent thermal conductivity enhancement effect and encapsulation effect, which can ensure the efficient thermal management of electronic devices, prevent the leakage of phase change materials from damaging electronic devices, support the miniaturization and high performance of electronic components, and promote the further development of chip thermal management materials science and engineering technology. Summary of the Invention

[0006] The object of the present invention is to provide a leakage-proof and highly thermally conductive composite phase change material and a preparation method thereof.

[0007] The innovation of the present invention lies in an integrated compatible phase change material encapsulation structure composed of one-dimensional / two-dimensional heterogeneous hybrid fillers and a continuous phase carbon source and subjected to surface treatment, which can provide an efficient heat transfer path for heat conduction; and a good liquid-phase phase change material encapsulation is formed through the hydrogen bond action between the phase change material and the surface modification coating layer to improve the leakage prevention performance of the structure.

[0008] To achieve the above-mentioned invention object, the technical solution of the present invention is:

[0009] A leakage-proof and highly thermally conductive composite phase change material, comprising raw materials with the following mass components: 100 parts of a carbon precursor solution, 10 - 40 parts of two-dimensional nano-fillers, 6 - 24 parts of surface-modified carbon nanofibers, and 900 - 1000 parts of a phase change material.

[0010] Further, the carbon precursor solution is composed of an aromatic dianhydride, an aromatic diamine, and triethylamine, and the molar ratio of the aromatic dianhydride, the aromatic diamine, and triethylamine is 1:1:2 - 3.

[0011] Further, the two-dimensional nano-fillers are one or a combination of graphene oxide, MXene nanosheets, and boron nitride nanosheets.

[0012] Further, the two-dimensional nano-fillers have a lateral size of 1 - 5 μm and a thickness of 3 - 5 nm.

[0013] Further, the surface-modified carbon nanofibers are obtained by modifying carbon nanofibers with a surface modifier. The diameter of the carbon nanofibers is 100 - 200 nm, and the length is 5 - 15 μm.

[0014] Further, the surface modifier is a 0.01 - 0.1 mol / L iodine solution or 30% hydrogen peroxide solution, and the modification treatment is carried out at room temperature; the thickness of the modification coating layer on the surface of the carbon nanofibers is 10 - 20 nm.

[0015] Further, the phase change material is a polyvinyl alcohol-based, fatty acid-based, or alcohol-based phase change material.

[0016] A preparation method of a leakage-proof and highly thermally conductive composite phase change material, comprising the following steps:

[0017] (1) Uniformly mix two-dimensional nanofillers and surface-modified carbon nanofibers in water according to the formula, and obtain one-dimensional / two-dimensional heterohybrid fillers through electrostatic adsorption. Add the one-dimensional / two-dimensional heterohybrid fillers to the carbon precursor solution, and through stirring and ultrasonic dispersion, make the one-dimensional / two-dimensional heterohybrid fillers uniformly dispersed in the carbon precursor solution. After directional freezing, vacuum freeze-drying, and high-temperature carbonization, a heterogenous carbon structure formed by the transformation of the one-dimensional / two-dimensional heterohybrid fillers and the precursor carbon source is obtained;

[0018] (2) Place the heterogenous carbon structure in a surface modifier solution containing dopamine hydrochloride. The surface modifier solution containing dopamine hydrochloride is heated to form a polydopamine modification coating both inside and outside the heterogenous carbon structure. After washing and drying, a surface-modified heterogenous carbon framework is obtained;

[0019] (3) Immerse the surface-modified heterogenous carbon framework in the melted phase change material, and through vacuum impregnation and natural cooling, a leakage-proof composite phase change material containing the surface-modified heterogenous carbon framework is obtained.

[0020] Furthermore, the concentration of the surface modifier solution containing dopamine hydrochloride is 0.25

[0021] ~1 mg / mL, and the thickness of the formed polydopamine modification coating is 20~120 nm.

[0022] Furthermore, the temperature required for directional freezing in step (1) is -150 °C, and the vacuum freeze-drying conditions are -50 °C and 10 Pa; the high-temperature carbonization temperature is 800~2800 °C.

[0023] The beneficial effects of the present invention are:

[0024] 1. In the present invention, the surface-modified carbon nanofibers carry the same charge and repel each other, enhancing their uniformity of dispersion in the solution and inhibiting the agglomeration and stacking of the nanofillers themselves. At the same time, the surface-modified carbon nanofibers and the two-dimensional nanosheets have opposite charges and will undergo electrostatic adsorption. Through electrostatic self-assembly, the one-dimensional surface-modified carbon nanofibers connect the dispersed two-dimensional nanosheets to form a one-dimensional / two-dimensional heterohybrid filler network with excellent dispersion; the introduced carbon precursor solution, as a high-quality carbon source, can weld well between the one-dimensional / two-dimensional heterogenous fillers, weaken the adverse effect of the filler interface on the heat transfer of the framework structure, and enable the fillers to form a good heat conduction path. At the same time, the one-dimensional / two-dimensional heterogenous fillers can, on the one hand, serve as a carbon template to induce the formation of a high-quality graphite structure during the carbonization process of the carbon precursor solution, and on the other hand, serve as a framework to effectively inhibit the shrinkage of the carbon precursor solution during the carbonization process. Finally, at a relatively low (~2.3 wt%) filler filling rate, the composite material obtains excellent thermal conductivity.

[0025] 2. In the present invention, the three-dimensional porous structure forms abundant hydrogen bonds with the phase change materials such as alcohols, acids, polyvinyl alcohols, etc. loaded inside through capillary action, surface tension, and the abundant oxygen-containing groups introduced by its surface modification, greatly enhancing the encapsulation ability of the three-dimensional porous structure for the phase change materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram for the preparation of the high thermal conductivity composite phase change material for preventing leakage.

[0027] Figure 2 Structure diagram of the surface-modified heterogeneous carbon skeleton.

[0028] Figure 3 Structure diagram of the high thermal conductivity composite phase change material for preventing leakage. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Example 1: A high thermal conductivity composite phase change material for preventing leakage, comprising raw materials with the following mass components: 100 parts of a carbon precursor solution, 10 parts of two-dimensional nano-fillers, 6 parts of surface-modified carbon nanofibers, and 1000 parts of a phase change material; the carbon precursor solution is composed of an aromatic dianhydride, an aromatic diamine, and triethylamine, and the molar ratio of the aromatic dianhydride, the aromatic diamine, and triethylamine is 1:1:2; the two-dimensional nano-fillers are graphene oxide; the transverse dimension of the two-dimensional nano-fillers is 1 - 5 μm, and the thickness is 3 - 5 nm; the surface-modified carbon nanofibers are obtained by modifying carbon nanofibers with a surface modifier, the diameter of the carbon nanofibers is 100 - 200 nm, and the length is 5 - 15 μm; the surface modifier is a 0.01 mol / L iodine solution, and the modification treatment is carried out at room temperature; the thickness of the modification coating on the surface of the carbon nanofibers is 10 nm; the phase change material is a polyvinyl alcohol-based phase change material. Example 2: A high thermal conductivity composite phase change material for preventing leakage, comprising raw materials with the following mass components: 100 parts of a carbon precursor solution, 25 parts of two-dimensional nano-fillers, 15 parts of surface-modified carbon nanofibers, and 950 parts of a phase change material; the carbon precursor solution is composed of an aromatic dianhydride, an aromatic diamine, and triethylamine, and the molar ratio of the aromatic dianhydride, the aromatic diamine, and triethylamine is 1:1:2.5; the two-dimensional nano-fillers are MXene nanosheets; the transverse dimension of the two-dimensional nano-fillers is 1 - 5 μm, and the thickness is 3 - 5 nm;

[0030] The surface-modified carbon nanofibers are obtained by modifying carbon nanofibers with a surface modifier, the diameter of the carbon nanofibers is 100 - 200 nm, and the length is 5 - 15 μm; the surface modifier is a 0.05 mol / L iodine solution or 30% hydrogen peroxide, and the modification treatment is carried out at room temperature; the thickness of the modification coating on the surface of the carbon nanofibers is 15 nm; the phase change material is a fatty acid-based phase change material.

[0031] Example 3: A leak-proof and highly thermally conductive composite phase change material, comprising raw materials with the following mass components: 100 parts of a carbon precursor solution, 40 parts of two-dimensional nano-fillers, 24 parts of surface-modified carbon nanofibers, and 900 parts of a phase change material; the carbon precursor solution is composed of an aromatic dianhydride, an aromatic diamine, and triethylamine, and the molar ratio of the aromatic dianhydride, the aromatic diamine, and triethylamine is 1:1:3; the two-dimensional nano-fillers are boron nitride nanosheets; the two-dimensional nano-fillers have a lateral size of 1 to 5 μm and a thickness of 3 to 5 nm;

[0032] The surface-modified carbon nanofibers are obtained by modifying carbon nanofibers with a surface modifier. The carbon nanofibers have a diameter of 100 to 200 nm and a length of 5 to 15 μm; the surface modifier is a 0.1 mol / L iodine solution, and the modification treatment is carried out at room temperature; the thickness of the modification coating on the surface of the carbon nanofibers is 20 nm; the phase change material is an alcohol-based phase change material.

[0033] Example 4: Referring to Example 1, the two-dimensional nano-fillers are one or a combination of several kinds of boron nitride nanosheets; the surface modifier is hydrogen peroxide with a concentration of 30%, and the modification treatment is carried out at room temperature.

[0034] Example 5: A preparation method of a leak-proof and highly thermally conductive composite phase change material, comprising the following steps:

[0035] (1) According to the formula of Example 1, the two-dimensional nano-fillers and the surface-modified carbon nanofibers are uniformly mixed in water, and a one-dimensional / two-dimensional heterojunction hybrid filler is obtained through electrostatic adsorption. The one-dimensional / two-dimensional heterojunction hybrid filler is added to the carbon precursor solution, and after stirring and ultrasonic dispersion, the one-dimensional / two-dimensional heterojunction hybrid filler is uniformly dispersed in the carbon precursor solution. After directional freezing, vacuum freeze-drying, and high-temperature carbonization, a heterostructured carbon structure formed by the conversion of the one-dimensional / two-dimensional heterojunction hybrid filler and the precursor carbon source is obtained. The temperature required for directional freezing is -150 °C, and the vacuum freeze-drying conditions are -50 °C and 10 Pa; the high-temperature carbonization temperature is 2800 °C;

[0036] (2) The heterostructured carbon structure is placed in a surface modifier solution containing 0.25 mg / mL of dopamine hydrochloride. The surface modifier solution containing dopamine hydrochloride is heated to form a polydopamine modification coating both inside and outside the heterostructured carbon structure. The thickness of the polydopamine modification coating is 20 nm. After washing and drying, a surface-modified heterostructured carbon skeleton is obtained;

[0037] (3) The surface-modified heterostructured carbon skeleton is impregnated in the melted phase change material, and through vacuum impregnation and natural cooling, a leak-proof composite phase change material containing the surface-modified heterostructured carbon skeleton is obtained.

[0038] Example 6: A preparation method of a leak-proof and highly thermally conductive composite phase change material, comprising the following steps:

[0039] (1) According to the formulation of Example 2, uniformly mix two-dimensional nano-fillers and surface-modified carbon nanofibers in water, and obtain one-dimensional / two-dimensional heterohybrid fillers through electrostatic adsorption. Add the one-dimensional / two-dimensional heterohybrid fillers to the carbon precursor solution, and after stirring and ultrasonic dispersion, make the one-dimensional / two-dimensional heterohybrid fillers uniformly dispersed in the carbon precursor solution. After directional freezing, vacuum freeze-drying, and high-temperature carbonization, a heterogenous carbon structure formed by the transformation of one-dimensional / two-dimensional heterohybrid fillers and the precursor carbon source is obtained. The temperature required for directional freezing is -150 °C, the vacuum freeze-drying conditions are -50 °C and 10 Pa; the high-temperature carbonization temperature is 1500 °C;

[0040] (2) Place the heterogenous carbon structure in a surface modifier solution containing dopamine hydrochloride with a concentration of 0.5 mg / mL. The surface modifier solution containing dopamine hydrochloride is heated to form a polydopamine modification coating both inside and outside the heterogenous carbon structure. The thickness of the polydopamine modification coating is 80 nm. After washing and drying, a surface-modified heterogenous carbon framework is obtained;

[0041] (3) Immerse the surface-modified heterogenous carbon framework in the melted phase change material, and through vacuum impregnation and natural cooling, obtain a leakage-proof composite phase change material containing the surface-modified heterogenous carbon framework.

[0042] Example 7: A preparation method of a leakage-proof and highly thermally conductive composite phase change material, comprising the following steps:

[0043] (1) According to the formulation of Example 3, uniformly mix two-dimensional nano-fillers and surface-modified carbon nanofibers in water, and obtain one-dimensional / two-dimensional heterohybrid fillers through electrostatic adsorption. Add the one-dimensional / two-dimensional heterohybrid fillers to the carbon precursor solution, and after stirring and ultrasonic dispersion, make the one-dimensional / two-dimensional heterohybrid fillers uniformly dispersed in the carbon precursor solution. After directional freezing, vacuum freeze-drying, and high-temperature carbonization, a heterogenous carbon structure formed by the transformation of one-dimensional / two-dimensional heterohybrid fillers and the precursor carbon source is obtained. The temperature required for directional freezing is -150 °C, the vacuum freeze-drying conditions are -50 °C and 10 Pa; the high-temperature carbonization temperature is 800 °C;

[0044] (2) Place the heterogenous carbon structure in a surface modifier solution containing dopamine hydrochloride with a concentration of 1 mg / mL. The surface modifier solution containing dopamine hydrochloride is heated to form a polydopamine modification coating both inside and outside the heterogenous carbon structure. The thickness of the polydopamine modification coating is 120 nm. After washing and drying, a surface-modified heterogenous carbon framework is obtained;

[0045] (3) Immerse the surface-modified heterogenous carbon framework in the melted phase change material, and through vacuum impregnation and natural cooling, obtain a leakage-proof composite phase change material containing the surface-modified heterogenous carbon framework.

[0046] Comparative Example 1: Referring to Example 5, the addition of surface-modified carbon nanofibers was cancelled.

[0047] Comparative Example 2: Referring to Example 5, the addition of two-dimensional nanofillers was cancelled.

[0048] Comparative Example 3: Referring to Example 5, the high-temperature carbonization temperature was adjusted to 600 °C.

[0049] Comparative Example 4: Referring to Example 5, the surface-modified carbon nanofibers were changed to carbon nanofibers. Comparative Example 5: Referring to Example 5, step (2) was cancelled.

[0050] The impregnation rate and leakage rate of the phase change material (PCM) in each example and comparative example are shown in Table 1.

[0051] Table 1

[0052]

[0053]

[0054] It can be seen from Table 1 that by comparing Examples 5 to 7 with Comparative Examples 1 to 5, the introduction of one-dimensional / two-dimensional heterogenous fillers effectively regulated the morphology of the carbon skeleton, further increasing the impregnation rate (enthalpy value) of the phase change material. The introduction of one-dimensional / two-dimensional heterogenous fillers and the high-temperature heat treatment process obtained a heterogenous carbon structure with excellent thermal conductivity. After its introduction, the thermal conductivity of the phase change material was significantly enhanced. In addition, the surface modification of the heterogenous carbon structure significantly reduced the liquid-phase leakage of the phase change material.

[0055] The described embodiments are only a part of the embodiments of the present invention, not all of them. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts fall within the scope of protection of the present invention.

Claims

1. A leak-proof and highly thermally conductive composite phase change material, characterized in that, Raw materials including the following mass components: 100 parts of carbon precursor solution, 10 - 40 parts of two-dimensional nano-fillers, 6 - 24 parts of surface-modified carbon nanofibers, and 900 - 1000 parts of phase change materials.

2. The anti-leakage and highly thermally conductive composite phase change material according to claim 1, wherein The carbon precursor solution is composed of aromatic dianhydride, aromatic diamine, and triethylamine, and the molar ratio of aromatic dianhydride, aromatic diamine, and triethylamine is 1:1:2 - 3.

3. The anti-leakage and highly thermally conductive composite phase change material according to claim 1, wherein The two-dimensional nano-fillers are one or a combination of graphene oxide, MXene nanosheets, and boron nitride nanosheets.

4. The anti-leakage and highly thermally conductive composite phase change material according to claim 1, wherein The lateral size of the two-dimensional nano-fillers is 1 - 5 μm, and the thickness is 3 - 5 nm.

5. The anti-leakage and highly thermally conductive composite phase change material according to claim 1, wherein The surface-modified carbon nanofibers are formed by modifying carbon nanofibers with a surface modifier. The diameter of the carbon nanofibers is 100 - 200 nm, and the length is 5 - 15 μm.

6. The anti-leakage and highly thermally conductive composite phase change material according to claim 5, wherein The surface modifier is 0.01 - 0.1 mol / L iodine solution or 30% hydrogen peroxide solution, and the modification treatment is carried out at room temperature; the thickness of the modification coating on the surface of the carbon nanofibers is 10 - 20 nm.

7. The anti-leakage and highly thermally conductive composite phase change material according to claim 1, wherein The phase change materials are polyvinyl alcohol-based, fatty acid-based, or alcohol-based phase change materials.

8. A method for preparing a leak-proof and highly thermally conductive composite phase change material as described in any one of claims 1 to 7, characterized in that, Including the following steps: (1) According to the formula, uniformly mix the two-dimensional nano-fillers and surface-modified carbon nanofibers in water to obtain one-dimensional / two-dimensional heterostructured hybrids through electrostatic adsorption. Add the one-dimensional / two-dimensional heterostructured hybrids to the carbon precursor solution, and through stirring and ultrasonic dispersion, make the one-dimensional / two-dimensional heterostructured hybrids uniformly dispersed in the carbon precursor solution. After directional freezing, vacuum freeze-drying, and high-temperature carbonization, obtain a heterostructured carbon structure formed by the transformation of one-dimensional / two-dimensional heterostructured hybrids and the precursor carbon source. (2) Place the heterostructured carbon structure in a surface modifier solution containing dopamine hydrochloride. The surface modifier solution containing dopamine hydrochloride is heated to form a polydopamine modification coating both inside and outside the heterostructured carbon structure. After washing and drying, obtain a surface-modified heterostructured carbon skeleton. (3) Immerse the surface-modified heterostructured carbon skeleton in the melted phase change material, and through vacuum impregnation and natural cooling, obtain a leakage-proof composite phase change material containing the surface-modified heterostructured carbon skeleton.

9. The preparation method of the leakage-proof and highly thermally conductive composite phase change material according to claim 8, characterized in that, The concentration of the surface modifier solution containing dopamine hydrochloride is 0.25 - 1 mg / mL, and the thickness of the formed polydopamine modification coating is 20 - 120 nm.

10. The preparation method of the leakage-proof and highly thermally conductive composite phase change material according to claim 8, characterized in that, In step (1), the temperature required for directional freezing is -150°C, the vacuum freeze-drying conditions are -50°C and 10 Pa; the high-temperature carbonization temperature is 800 - 2800°C.

Citation Information

Patent Citations

  • Three-dimensional graphene-magnetic particle hybrid skeleton composite phase change material and preparation method thereof

    CN118344850A

  • Thermally conductive and leak-proof polyethylene glycol composite phase change material and preparation method thereof

    CN118580840B

Cited By

  • Preparation method of high-thermal-conductivity intrinsic solid-solid phase change polyamide elastomer nanofiber and product thereof

    CN121295380A